2018
DOI: 10.1002/smll.201800240
|View full text |Cite
|
Sign up to set email alerts
|

Vertical ZnO Nanotube Transistor on a Graphene Film for Flexible Inorganic Electronics

Abstract: The bottom-up integration of a 1D-2D hybrid semiconductor nanostructure into a vertical field-effect transistor (VFET) for use in flexible inorganic electronics is reported. Zinc oxide (ZnO) nanotubes on graphene film is used as an example. The VFET is fabricated by growing position- and dimension-controlled single crystal ZnO nanotubes vertically on a large graphene film. The graphene film, which acts as the substrate, provides a bottom electrical contact to the nanotubes. Due to the high quality of the singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The ZnO NWs were preferably grown on graphene, while no growth was observed on the SiO 2 surface. Position-controlled hydrothermal growth of ZnO micro/nanostructures on graphene has been reported by several research groups [ 20 , 21 , 22 , 23 ]. Earlier, ZnO seed layers were employed to promote the growth of ZnO structures.…”
Section: Resultsmentioning
confidence: 99%
“…The ZnO NWs were preferably grown on graphene, while no growth was observed on the SiO 2 surface. Position-controlled hydrothermal growth of ZnO micro/nanostructures on graphene has been reported by several research groups [ 20 , 21 , 22 , 23 ]. Earlier, ZnO seed layers were employed to promote the growth of ZnO structures.…”
Section: Resultsmentioning
confidence: 99%
“…Vertically oriented nanostructures such as nanowires, nanopillars, and nanotubes possess the distinct advantages of having high surface area, high coverage density, directional charge transport, and light trapping capability. [1][2][3] These characteristics make them especially attractive for applications in electronics, 4 optoelectronics, 5,6 energy storage, 7,8 bioelectronics, 9 catalysis, 10 and sensors. 11 For example, the light trapping capability of vertically oriented silicon-based nanowires has led to high efficiency solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Direct growth of 2D or 3D materials on other 2D and 3D materials has advantages over stacking. van der Waals (vdW) and remote epitaxy techniques have shown that 2D material-embedding heterostructures with clean and abrupt interfaces can be prepared in a manner compatible with mass production. ,, Especially, remote epitaxy based on lattice transparency of an atomically thin 2D material is of great interest because the technique has high potential as a way to investigate the epitaxy mechanism across vdW gap, and for scalable and economical manufacturing of semiconductor devices. In principle, remote epitaxy can be widely used because the absence of surface dangling bonds on a 2D material eliminates the problem of material incompatibility, a critical bottleneck of covalent and ionic bonding-based conventional epitaxy. Previous reports have established that remote epitaxy can be applied for various 3D materials. ,,, Nevertheless, the only 2D material that can currently be used as a substrate for remote epitaxy is graphene.…”
Section: Introductionmentioning
confidence: 99%